Implementation Of Organizational Culture And Job Satisfaction Through Employee Performance At PT. Traktor Kuning Deli Serdang - Surya Darma; Annio Indah Lestari Nasution; Purnama Ramadani Silalahi (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
Organizational culture is now a major focus in the business world due to the various benefits it offers. This culture creates an internal company atmosphere that can spur creativity and motivation, leading to increased work performance. With a solid and positive organizational culture, company performance can improve significantly, boosting productivity and effectiveness. Furthermore, job satisfaction is a crucial factor influencing employee performance. Employers need to pay special attention to job satisfaction and work motivation to boost individual and overall organizational performance. Excellent employee performance will ultimately improve the quality and efficiency of the company or organization. This research is a descriptive study with a qualitative approach. To achieve this objective, the data collection technique used data collection through interviews and documentation. Interviews were conducted directly with sources (informants) involved in PT Traktor Kuning, namely the Deputy Manager of PT Traktor Kuning, the Head of IT at PT Traktor Kuning Deli Serdang, and PSDS Deli Serdang employees.